'That was a good move'—Some remarks on the (ir)relevance of 'narratives of secularism' in everyday politics in Bangladesh. (June 2020) - Schulz, Mascha
This article explores the complex role of political ideologies in everyday politics and for urban middle-class Bangladeshis' evaluation of political parties. Drawing on long-term ethnographic research and, more specifically, conversations and contentions around the removal of 'Lady Justice' from the front of the Supreme Court of Bangladesh in 2017, I show that although the Awami League continues to be considered a 'secular party', many people do not believe that the Awami League is implementing secular policy and criticise it for what they perceive as 'hypocrisy'. I argue that this seemingly paradoxical situation can be explained by a political structure that is marked by high factionalism and party competition. Data from research among politicians and the left-leaning, so-called 'culturally-minded' milieu in Sylhet, shows that certain segments of the educated middle class acknowledge the pragmatic realities of politics and do not expect the Awami League to act 'progressively'. Nonetheless, they continue to position the party's 'progressive' and 'secular' ideological basis as a primary reason for supporting the party. The article thus contributes to a deeper understanding of contemporary popular and elite practices and perceptions of party politics, democracy, and what might be labelled the 'party-state effect'.